Heavy metals content in Paraphilometroides nemipteri from South China Sea may influence level of glutathione and P38 protein expression - Nurul Huda Abd Kadir; Mohd Fauzi Mahmud; Mohamad Khairi Mohd Zainol; Mastura Abd Malek; Faizah Shaharom Harrison (Penerbit Universiti Kebangsaan Malaysia, 2018)
Numerous studies have shown that parasites potentially become bio-accumulators for heavy metals. The heavy metals content in parasite-infected fish was reported to be lower compared to the parasite non-infected fish. Evaluation of heavy metal content in Nemipterus peronii and Paraphilometroides nemipteri was performed using ICP-OES. Our result has shown that arsenic was the most abundance heavy metal content in muscle N. peronii and P. nemipteri, suggesting that the parasite has the ability to accumulate heavy metals. Heavy metals were reported to induce oxidative stress where glutathione and p38 protein may be involved. Thus, expression of the p38 protein was determined using western blot technique and glutathione content was measured fluorometrically. The p38 expression in P. nemipteri of Pulau Kambing was higher compared to P. nemipteri of Besut has shown that the parasite may exposed to stress. Glutathione content showed no significant changes due to detoxification mechanism occurred in the parasite. In this study, we could conclude that P. nemipteri could be a bio-accumulator, whereas p38 protein and glutathione as indicator of stress level in the parasite that exposed to the heavy metals.